Investigating infant development through an interprofessional research collaboration: case report. (2nd March 2021) - Devine, Nancy; Gee, Bryan M; Aubuchon-Endsley, Nicki L; Brumley, Michele R; Ramsdell, Heather L; Swann-Thomsen, Hillary E
Abstract : Background/aims: From a dynamic systems perspective of infant development, several systems (eg sensorimotor, perceptual, and reasoning, among others, may self-organise and change behavioural responses over time following experience. These changes in infant behaviour are often measured through the achievement of age-adjusted developmental milestones. However, the majority of research guiding the understanding of typical infant developmental trajectories rarely depicts collaborations across more than one or two disciplines. The purpose of this case report was to describe an interprofessional research collaboration among researchers and clinicians in clinical and experimental psychology, occupational therapy, speech-language pathology, and physical therapy to establish methods and procedures that describe different developmental domains in infancy for a single participant. Methods: One infant who was typically developing was video and audio recorded during 60 minutes of free play at ages 8, 12, and 16 months. Four research labs scored the middle 20 minutes of recorded time for infant and caregiver utterances, touch and motor behaviours, play participation and performance, co-occupation, and caregiver sensitivity to infant affect. The combined data from the four labs captured and revealed a rich description of the infant's development from 8 to 16 months of age. Results: The data for this single infant indicated that important developmental changes occurred leading to greater independence in communication, mobility and co-occupation, while reducing some of the requirements for attention from the caregiver. Conclusions: The procedures used within research labs by principal investigators from four disciplines to describe development in a single infant between 8 and 16 months of age yielded a rich example of development, consistent with published milestones. Future studies with larger sample sizes using the interdisciplinary research methods applied in this case study may improve the understanding of, influences on, and relationships between, infant developmental trajectories.